Impact of Exchange Rate Movements on Exports: An Analysis of Indian Non-Financial Sector Firms - Yin-Wong Cheung; Rajeswari Sengupta (Center for Economic Studies and ifo Institute (CESifo), 2013)
We explore the real effective exchange rate (REER) effects on the share of exports of Indian non-financial sector firms for the period 2000 to 2010. Our empirical analysis reveals that, on average, there has been a strong and significant negative impact of currency appreciation as well as currency volatility on Indian firms' export shares. The labor costs are found to intensify the exchange rate effects on trade. Further, there is evidence that these Indian firms respond asymmetrically to exchange rates. For instance, the REER change effect is likely to be driven by a negative appreciation effect but not so much a depreciation effect. Also, Indian firms that have smaller export shares tend to have a stronger response to both REER change and volatility. Compared with those exporting goods, the firms that export services are more affected by exchange rate fluctuations. The findings, especially those on asymmetric responses, have important policy implications.
Keywords: F10; F40; 330; exchange rate fluctuations; firm-level export shares; asymmetric effects; services exports